2021
DOI: 10.3390/ijerph18094437
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Physical Activity, Sunshine Duration and Osteoporosis According to Obesity and Other Lifestyle Factors: A Nested Case–Control Study

Abstract: (1) Background: The purpose of the study was to evaluate the associations between physical activity (PA), sunshine duration (SD) and the occurrence of osteoporosis according to lifestyle status. (2) Methods: Data from the Korean National Health Insurance Service–National Sample Cohort (NHIS-NSC) collected from 2009 to 2015 were used. Osteoporosis (n = 19,351) and control (n = 38,702) participants were matched in a 1:2 ratio according to age, sex, income, and region of residence. PA was classified as moderate- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Our previous study, which used the same national cohort data and meteorological data as our present study, found that a long sunshine duration (SD) and higher intensity PA were associated with a lower occurrence of osteoporosis [17]. A study using national cohort data from Korea also reported that PA was associated with low fracture risk regardless of the type of PA and site of fracture [18].…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…Our previous study, which used the same national cohort data and meteorological data as our present study, found that a long sunshine duration (SD) and higher intensity PA were associated with a lower occurrence of osteoporosis [17]. A study using national cohort data from Korea also reported that PA was associated with low fracture risk regardless of the type of PA and site of fracture [18].…”
Section: Introductionsupporting
confidence: 64%
“…Because the PA information was different from 2002 to 2008, those participants and participants without PA records were removed (n = 33,337 in the osteoporotic fractures group; n = 57,788 in the control group). In the osteoporotic fractures group, participants who did not undergo the BMD test before the first fracture diagnosis (index date) were excluded (n = 10,875; claim codes were described elsewhere [17]). In the control group, participants who did not undergo the BMD test from 2002 to 2015 were excluded (n = 277,717).…”
Section: Study Population and Participant Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, excessive use or abuse of alcohol, 15,79–82 caffeine, 83,84 and carbonated drinks 83 should be avoided, which are harmful for both health people and patients with osteoporosis. On the other hand, any form of nicotine should be discouraged 85,86 .…”
Section: Risk Factors and Mechanisms For Osteoporosis In Copdmentioning
confidence: 99%